Early life outcomes of prenatal exposure to alcohol and synthetic cannabinoids in mice - Siara K. Rouzer; McKay Domen; Aisley George; Abigail Bowring; Rajesh C. Miranda (Drug and Alcohol Dependence Reports, 2025)
Purpose: This study investigated the effects of prenatal co-exposure to alcohol and synthetic cannabinoids on offspring viability, physical development, and neurobehavioral outcomes in young adulthood. The goal of this investigation was to determine whether prenatal co-exposure produced distinct outcomes from single-drug exposures, including sex-specific vulnerabilities in motor coordination and exploratory behaviors. Methods: Pregnant C57Bl/6 J mice were randomly assigned to one of four treatment groups: drug-free controls, alcohol (ALC)-exposed, cannabinoid (CP-55,940, CB)-exposed or ALC+CB-exposed, with drug exposure occurring between Gestational Days 12–15. Offspring viability, physical malformations, and developmental delays were first assessed at birth. Then, behavioral evaluations, including rotarod and open field tests, were conducted on young adult offspring (Postnatal Days 100–120). Results: ALC+CB exposure significantly decreased litter survival (p = 0.006) and offspring viability compared to controls. Non-viable offspring exhibited craniofacial abnormalities, limb malformations, and developmental delays. Assessments of rotarod performance revealed that all exposures reduced motor coordination in males compared to controls (p < 0.05), while ALC and CB exposures alone produced this outcome in females. Open field tests indicated that ALC+CB exposure reduced time in the center of the arena in male offspring exclusively, while this same exposure increased hyperactivity compared to single-drug and control groups, independent of sex (p < 0.05). Conclusions: Prenatal co-exposure to alcohol and synthetic cannabinoids exacerbated offspring mortality and induced sex-specific deficits in neurobehavioral motor outcomes. These findings highlight the distinct risks of polysubstance exposure during pregnancy and underscore the need for targeted interventions to mitigate the effects of prenatal polysubstance exposure on offspring health outcomes.